Multi-scale model for the structure of hybrid perovskites: analysis of charge migration in disordered MAPbI3 structures - Jari Järvi; Jingrui Li; Patrick Rinke (New Journal of Physics, 2018)
We have developed a multi-scale model for organic–inorganic hybrid perovskites (HPs) that applies quantum mechanical (QM) calculations of small HP supercell models to large coarse-grained structures. With a mixed quantum–classical hopping model, we have studied the effects of cation disorder on charge mobilities in HPs, which is a key feature to optimize their photovoltaic performance. Our multi-scale model parametrizes the interaction between neighboring methylammonium cations (MA ^+ ) in the prototypical HP material, methylammonium lead triiodide (CH _3 NH _3 PbI _3 , or MAPbI _3 ). For the charge mobility analysis with our hopping model, we solved the QM site-to-site hopping probabilities analytically and computed the nearest-neighbor electronic coupling energies from the band structure of MAPbI _3 with density-functional theory. We investigated the charge mobility in various MAPbI _3 supercell models of ordered and disordered MA ^+ cations. Our results indicate a structure-dependent mobility, in the range of 50–66 cm ^2 V ^−1 s ^−1 , with the highest observed in the ordered tetragonal phase.